TWELFTH CONFERENCE ON CLIMATE CHANGE AND DEVELOPMENT IN AFRICA (CCDA-XII): FINANCING CLIMATE ADAPTATION AND RESILIENCE IN AFRICA - Amha, Yosef; Demissie, Teferi (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
The Twelfth Conference on Climate Change and Development in Africa (CCDA-XII) took place from August 30 to September 2, 2024, in Abidjan, Côte d'Ivoire. The report provides an overview of the event's objectives, discussions, outcomes, and personal reflections from attending and co-organizing this significant gathering. The conference brought together over 300 stakeholders from various countries to address the challenges of climate change in Africa, with a focus on "Financing Climate Adaptation and Resilience in Africa." The event was organized by ClimDev Africa(AUC, UNECA, and AfDB) in partnership with PACJA, WMO, AICCRA, CIFOR-World Agroforestry, SEI, UN Environment, EAC, UNFCCC, AMCEN, AFDAN, UNDP, IPCC, ACSEA, The Climate Champions Team, and the Government of Côte d'Ivoire.